PELATIHAN MULTIMEDIA VIRTUAL INTERAKTIF BERBASIS TEKS DESKRIPSI UNTUK PENDIDIKAN GURU SEKOLAH DASAR DI KEPULAUAN SERIBU - Herlina Usman; Miftahulkhairah Anwar (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract This community dedication aims to provide virtual training assistance to elementary school teachers in the Kepulauan Seribu Regency of DKI Jakarta, which is done by providing training on the use of interactive multimedia learning based on text descriptions in learning to develop the ability of teachers to use learning media in class. Learning media includes everything that can channel messages, which can stimulate the thoughts, feelings, and willingness of students so that they can encourage the creation of a learning process in students. By using interactive multimedia based on text descriptions, it is hoped that a teacher should be able to be creative in teaching by involving the cognitive level of higher-thinking hierarchies that are implied from Bloom's Taxonomy. The method used in this mentoring activity is virtual training. The service material includes material related to making interactive multimedia based on text descriptions for language learning in elementary schools. The target audience for Community Service is the Primary School Teachers of the Thousand Islands Regency, DKI Jakarta Province. The program output targets are: 1) The teacher has insight and understanding of learning using interactive multimedia in the learning process. 2) Teachers are able to make learning tools including lesson plans, teaching materials, LKPD, learning media, and evaluation. 3) The teacher is able to carry out learning using interactive multimedia in the learning process. 4) The teacher is able to design a class with the application of Interactive Multimedia based on Text Description. Abstrak Pengabdian masyarakat ini bertujuan untuk memberikan pendampingan pelatihan virtual kepada Guru-guru Sekolah Dasar Kabupaten Kepulauan Seribu provinsi DKI Jakarta, yang dilakukan adalah dengan memberikan pelatihan pemanfaatan pembelajaran Multimedia Interaktif berbasis diskripsi teks dalam pembelajaran untuk mengembangkan kemampuan guru-guru dalam menggunakan media pembelajaran di kelas. Media pembelajaran meliputi segala sesuatu yang dapat menyalurkan pesan, yang dapat merangsang fikiran, perasaan, dan kemauan peserta didik sehingga dapat mendorong terciptanya proses belajar pada diri peserta didik. Dengan menggunakan multimedia interaktif berbasis diskripsi teks diharapkan seorang guru sebaiknya dalam mengajar dapat berkreasi dengan melibatkan level kognitif hierarki berpikir tinggi yang di canamkan dari Taksonomi Bloom, Metode yang digunakan dalam kegiatan pendampingan ini adalah pelatihan dengan virtual. Materi pengabdian meliputi materi yang berkaitan dengan pembuatan multimedia interaktif berbasis diskripsi teks untuk pembelajaran bahasa di Sekolah Dasar. Khalayak sasaran Pengabdian kepada Masyaraka adalah Guru-guru Sekolah Dasar Kabupaten Kepulauan Seribu provinsi DKI Jakarta , Target luaran program adalah: 1) Guru mempunyai wawasan dan pemahaman tentang pembelajaran dengan menggunakan Multimedia Interaktif dalam proses pembelajaran. 2) Guru mampu membuat perangkat pembelajaran meliputi RPP, Bahan Ajar, LKPD, Media pembelajaran, dan evaluasi. 3) Guru mampu melaksanakan pembelajaran dengan menggunakan Multimedia interaktif dalam proses pembelajaran. 4) Guru mampu mendisain kelas dengan penerapan penggunaan Multimedia Interaktif berbasis Diskripsi Teks.